PENGARUH KECERDASAN EMOSI DAN BURNOUT TERHADAP KINERJA KARYAWAN INSTITUT AGAMA ISLAM SYARIFUDDIN WONOREJO LUMAJANG - Bambang Subahri (Dakwatuna: Jurnal Dakwah dan Komunikasi Islam, 2017)
This study aims to determine the influence of emotional intelligence and burnout on the Employee performance of Institut Agama Islam Syarifuddin (Syarifuddin Islamic Institute), Wonorejo, Lumajang. The instrument used in this study is the Performance approach based on Sabine Sonnentag’s theory (2010); the applied scale-based emotional intelligence is one that developed by Daniel Goleman (2003) and the employed scale of burnout is a scale formulated by Maslach and Jackson (1982). The result indicates the existence of effect of emotional intelligence and burnout on the employees’ performance.